ABOUT COMPILED CATALOGUE OF SPECTROSCOPICALLY DETERMINED α-ELEMENTS ABUNDANCES FOR STARS WITH ACCURATE PARALLAXES - Borkova, T. V.; Katchieva, M. S.; Marsakov, B. A.; Pitkina, D. M. (Одеські астрономічні публікації, 2007)
We present a new version of the compiled catalogue of nearby stars for which was published the spectoscopically determined effective temperatures, surface gravities, and abundances of iron, magnesium, calcium, silicon, and titanium. Distances, velocity components, galactic orbital elements, and ages was calculated for all stars. The atmospheric parameters and iron abundances were found from 4700 values in 136 publications, while relative abundances of alpha-elements were found from 2800 values in 81 publications for ≈ 2000 dwarfs and giants using a three-step iteration averaging procedure, with weights assigned to each source of data as well as to each individual determination and taking into account systematic deviations of each scale relative to the reduced mean scale. The estimated assumed completeness for data sources containing more than five stars, up to late April 2007, exceeds 90 For the vast majority of stars in the catalogue, the spatial-velocity components were derived from modern high-precision astrometric observations, and their Galactic orbit elements were computed using a three-component model of the Galaxy, consisting of a disk, a bulge, and a massive extended halo. Ages was determined for dwarfs and subgiants using Yale isochrones 2004. For this purpose the original codes was developed, based on interpolation with the 3D-spline functions of theoretical isochrones, and with subsequent interpolation in metallicity and abundances of α-elements.